Inhibition of Staphylococcus aureus cocktail using the synergies of oregano and rosemary essential oils or carvacrol and 1,8-cineole - Honório, Vanessa G.; Bezerra, Jéssica; Souza, Geany T.; Carvalho, Rayssa J.; Gomes-Neto, Nelson J.; Figueiredo, Regina C. B. Q.; Melo, Janaína V.; Souza, Evandro L.; Magnani, Marciane (Frontiers in Microbiology, 2015)
This study assessed the inhibitory effects of the essential oils (EOs) from Origanum vulgare L. (OVEO) and Rosmarinus officinalis L. (ROEO), as well as of the its majority individual constituents (ICs) carvacrol (CAR) and 1,8-cineole (CIN), respectively, combined at subinhibitory concentrations against a cocktail of Staphylococcus aureus. The Minimum inhibitory Concentration (MIC) of both OVEO and CAR against S. aureus cocktail was 1.25 μL/mL, while for ROEO and CIN the MIC value was 10 μL/mL. The Fractional Inhibitory Concentration Index of the combined EOs or ICs was ≤0.5 indicating a synergic interaction. The incorporation of OVEO and ROEO or CAR and CIN at different combinations in cheese and meat broths caused a decrease (p ≤ 0.05) of initial counts of S. aureus. Combined application of 1/8 MIC OVEO and 1/4 MIC ROEO or 1/4 MIC CAR and 1/4 MIC CIN in meat and cheese samples reduced (p ≤ 0.05) the viable cells counts and caused morphological changes in S. aureus cells, such as cell shrinkage and appearance of blebbing-like structures on cell surfaces. However, in cheese and meat samples the decrease in viable cell counts was smaller (p ≤ 0.05) than that observed in cheese and meat broths. These findings reinforce the potential of the use of OVEO and ROEO or CAR and CIN in combination to control S. aureus in cheese and meat matrices.